Implikasi Promosi dan Citra Merek Terhadap Minat Melalui Kualitas Pelayanan pada PT. Jalur Nugraha Ekakurir (JNE) - Syelvi Adelia; Zaharuddin Zaharuddin; Sitta Kusuma (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine and analyze the extent of the influence of Promotion on Service Quality at PT Jalur Nugraha Ekakurir (JNE). To determine and analyze the extent of the influence of Brand Image on Service Quality at PT Jalur Nugraha Ekakurir (JNE). To determine and analyze the simultaneous influence of Promotion and Brand Image on Service Quality at PT Jalur Nugraha Ekakurir (JNE). To determine and analyze the extent of the influence of Service Quality on Interest at PT Jalur Nugraha Ekakurir (JNE). To determine and analyze the simultaneous influence of Promotion and Brand Image on Interest at PT Jalur Nugraha Ekakurir (JNE). The population studied is 19,962 consumers of PT Jalur Nugraha Ekakurir (JNE) in the 2024 period. The sampling technique used is Probability Sampling with the Simple Random Sampling technique, and the sample in this study was measured using the Slovin formula, resulting in 100 respondents. The data collection techniques used in this research are questionnaires and observation. This study is designed using a descriptive method with a quantitative approach by using SmartPLS 3.0. The results of the study show that 1) There is a positive and significant influence of Promotion on Service Quality at PT Jalur Nugraha Ekakurir (JNE). This is evidenced by a path coefficient of 0.320 and a p-value of 0.000. 2) There is a positive and significant influence of Brand Image on Service Quality at PT Jalur Nugraha Ekakurir (JNE). This is evidenced by a path coefficient of 0.578 and a p-value of 0.000. 3) There is a positive and significant simultaneous influence of Promotion and Brand Image on Service Quality at PT Jalur Nugraha Ekakurir (JNE). This is indicated by an R Square value of 0.951 or 95.1%. 4) There is a positive and significant influence of Service Quality on Interest at PT Jalur Nugraha Ekakurir (JNE). This is evidenced by a path coefficient of 0.807 and a p-value of 0.000. 5) There is a positive and significant simultaneous influence of Promotion and Brand Image on Interest at PT Jalur Nugraha Ekakurir (JNE). This is indicated by an R Square value of 0.951 or 95.1%.